Acute surgical management - Hwang, N. C. (Nian Chih), 1960-; Ooi, London Lucien (World Scientific : SGH Postgraduate Medical Institute, 2004)
Acute surgical emergencies constitute one of the main clinical aspects that a doctor in hospital practice is expected to handle and manage. This book addresses some of the important and common acute surgical conditions, and has been written from an Asian perspective.